Investigation on shear induced isothermal crystallization of poly (lactic acid) nanocomposite based on graphene. Issue 1 (2nd January 2017) - Reghat, Mojdeh; Ghasemi, Ismaeil; Farno, Ehsan; Azizi, Hamed; Namin, Parvin Ehsani; Karrabi, Mohammad
ABSTRACT: In this study, the isothermal crystallization of poly (lactic acid) (PLA) and its graphene-based nanocomposites (containing 0.5, 1, 2, and 3 wt% of graphene nanoplatelets – GNp) was studied at 135°C under quiescent and different presheared conditions (0.1, 0.3, 0.5, 1.1, and 1.8 s for 60s). Induction time of crystallization was determined from the plot of storage modulus versus time in time sweep test. Results showed that increase in GNp content decreased the induction time significantly. The preshear flow did not significantly affect the induction time of PLA containing 0.5 wt% of GNp and neat PLA. However, an increase in the intensity of preshear for graphene-based nanocomposites containing 1, 2, and 3 wt% of GNp first decreased the induction time and then increased it. The induction time also decreased with increase in the duration of shear flow.